SOSIALISASI PROSES PRODUK HALAL BAGI UMKM DI KOTA SAMARINDA - Sugiarto Sugiarto; Swadia Gandhi Mahardika; Abiyajid Bustami (Wadah Inovasi Indonesia, 2022)
TMNI Coffee Shop in Jl. VII Pemuda. This results in a standard education and statistical analysis for each product. This is achieved through the use of a device that employs ceramic technology and is installed in a jawab. The result demonstrates the effectiveness of the program for the general public. The aforementioned socialization rangkaian was utilized by a number of individuals. As a result of participating in the aforementioned workshop, warga Kecamatan Siulak Deras Gunung Kerinci will be able to demonstrate the ability to manufacture halal-label products and the process of manufacturing them in accordance with halal standards.